Continuous and intermittent heat acclimation and decay in team sport athletes. Issue 3 (16th March 2019) - Duvnjak-Zaknich, Daniel M.; Wallman, Karen E.; Dawson, Brian T.; Peeling, Peter
Abstract: The aim of this study was to compare the impact of continuous (CON) and intermittent (INT) heat acclimation protocols on repeat-sprint performance, and to also assess the degree of performance decay following acclimation. Using a pair-matched, between subjects design, 16 trained male team sport athletes were allocated to either INT (8 sessions over 15 days) or CON acclimation (8 sessions over 8 days) groups. Participants performed a heat tolerance test (HTT) involving 60-min of repeat-sprint cycling with a 10-min half time break (in 35.3 ± 0.7°C, 60.1 ± 4.0%; RH) two days pre- (pre-HTT) and post-acclimation (post-HTT1). Decay was investigated with two further HTT's completed over the next two weeks (post-HTT2 and post-HTT3). Results showed the post-HTT1 performance variables [mean power (pre-HTT; INT = 1002.07 ± 173.74, CON = 1057.10 ± 180.07 / post-HTT1; INT = 1097.11 ± 186.85, CON = 1163.77 ± 184.65 W), mean power (W.kg −1 ), total work (kJ) and work (J.kg −1 )] were greater than pre-HHT ( p < 0.001) after acclimation, with no differences between INT and CON. No differences in final core and mean skin temperatures or heart rate existed after INT or CON acclimation, however 30 min measures for thermal sensation, perceived thirst and ratings of perceived exertion (as well as the final measure) were lower in post-HTT1 ( p < 0.05) in CON. Performance and thermoregulatory responses in post-HTT2 and 3 were similar to post-HTT1 in both INT and CON. These results indicate that prolonged repeat-sprint exercise in the heat is improved after acclimation involving short, high-intensity cycling sessions using either CON or INT protocols, with performance well-maintained over the subsequent 2 weeks, despite removal of the heat stimulus.